Tradability Index: A Comprehensive Measure for the Tradability of Output - Alexandra Bykova; Roman Stöllinger (The Vienna Institute for International Economic Studies (wiiw), 2017)
This paper describes the main features of a measure for the specialisation in producing tradable output which is labelled tradability index. It is based on the assumption that all sectors produce goods and services that are tradable but to varying degrees. Therefore, while all sectors produce tradable output, the extent of the tradability varies across sectors depending on their export orientation at the global level. Combined with the economic structure of countries, the tradability of sectors can be used to calculate the tradability index. This technical paper explains the basic concepts of the tradability index and provides information on the underlying data.
Keywords: F10; F40; 330; tradability of output; tradability index; export openness; value added exports